PERAN KEBIJAKAN DAN KELEMBAGAAN PERTANIAN TERHADAP KEBERHASILAN USAHATANI BUNGA KRISAN (Chrysanthemum sp) POTONG (Suatu Kasus Petani Bunga Krisan di Kecamatan Sukaresmi, Kabupaten Cianjur, Jawa Barat) - Yatti Rachmawati; Euis Dasipah; Karyana KS (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2022)
This study aims to determine the effect of Agricultural Policy and Agricultural Institutions on the Success of Cut Chrysanthemum Flower Farming. The method used is a survey of farmers in Sukaresmi District, Cianjur Regency. Data was taken from August 2021 to October 2021 based on the census technique obtained by 70 respondents. The analytical technique for testing the hypothesis used is SEM (Structural Equetion Modeling). The results obtained from the research on the role performance of agricultural policies in the context of the success of cut chrysanthemum farming in Sukaresmi District, Cianjur Regency, which include: Production input policies; Marketing Policy; Research Policy; and credit policy obtained an achievement level of 63.57 % with good criteria. Performance of the Role of Agricultural Institutions which includes: Production input institutions; Marketing Institutions; Financial Institutions; Farmer Group Institutions; and Research Institutions in the context of the success of cut chrysanthemum farming in Sukaresmi District, Cianjur Regency, obtained an achievement rate of 68.25%, good criteria. The performance of the success of cut chrysanthemum farming in Sukaresmi District, Cianjur Regency, which consists of: Quality; Productivity; continuity ; and the level of profit of farming obtained an achievement level of 66.70%, the criteria are Good. There is a fairly strong relationship between Agricultural Policy and Agricultural Institutions as indicated by a correlation coefficient of 0.89. The better the Agricultural Policy, the better the agricultural institutions and vice versa. Agricultural policies and agricultural institutions have a positive effect on the success of chrysanthemum cut flower farming. The total influence of agricultural policies on farming success is 6.91%, and the total influence of agricultural institutions is 83.71%. The higher/better Agricultural Policy and Agricultural Institutions, the success of chrysanthemum cut flower farming will be higher.